Prevalence and factors associated with burnout syndrome in resident physicians: A cross-sectional study in Italy - Luca DI GIAMPAOLO; Andrea ROSSETTI; Teresa GALANTI; Simone DE SIO; Luca COPPETA; Hector NIETO; Hiroo WADA; Niu QUIAO; Younes RAMI; Hicham KHABBACHE; Driss AIT ALI; Amelia RIZZO; et al. (Journal of Health and Social Sciences)
Introduction: Burnout syndrome is a psychological condition marked by emotional exhaustion, depersonalization, and diminished personal accomplishment due to chronic workplace stress. Despite its significance, few studies have specifically documented burnout levels among resident physicians. This study aims to assess the prevalence of burnout and its associated factors within this population. Methods: We conducted a cross-sectional survey involving 160 resident physicians in Italy. To evaluate levels of emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA), we utilized the Maslach Burnout Inventory. Additionally, we assessed work-life balance using questions related to Free-time satisfaction (FTS), Free-Time Satisfaction Reduction (FTRS), and Work-problems pervasiveness (WPP). Results: The analysis revealed that 30% of residents had high levels of emotional exhaustion, with an equal percentage reporting low levels. For depersonalization, 26.88% of participants reported high levels. In contrast, only 3.75% of residents report high levels of personal accomplishment. Furthermore, our findings indicate that only work-related factors influence burnout levels in our sample. Discussion: Consistent with previous research, our results demonstrate higher levels of emotional exhaustion and depersonalization, and lower levels of personal accomplishment among resident physicians. These findings support existing studies that burnout is strongly associated with work-related factors over individual-level demographic factors. Furthermore, residents who maintain a good work-life balance report lower burnout levels compared to those who struggle to achieve this balance.